ANALISIS KINERJA BADAN PENANGGULANGAN BENCANA DAERAH KABUPATEN KARO DALAM UPAYA PENANGGULANGAN BENCANA ERUPSI GUNUNG SINABUNG DI KABUPATEN KARO - Suri, Nur Khotimah (PERSPEKTIF, 2016)
The intent and purpose of this study was to determine how the performance of the Regional Disaster Management Agency in the Karo District Disaster Relief Efforts eruption of Mount Sinabung, to know what obstacles faced by the Regional Disaster Management Agency in the Karo District Disaster Relief Efforts eruption of Mount Sinabung. The method used in this research is descriptive qualitative method, which uses the theory of an explanatory research with a view to interpreting the phenomena occurring in the performance of Regional Disaster Management Agency Karo in Efforts for Disaster Management eruption of Mount Sinabung and done by involving a variety of data collection techniques exist. Produce and process the data descriptive nature, such as interviews and direct observation.